Satu Malaysia dalam Neraca Satu Ummah - Yusri Mohamad Ramli (Buletin Al-Turas, 2010)
The concept One Malaysia by Datuk Seri MOhd Najib Tun Abdul Razak has become a kinetic strength for the development of the kingdom under his ruling. With the vision of uniting the Malaydsians who are varied in religionrace, it becomes a key agenda in every action and consideration of the kingdom. From islamic point of view. Rasulullah saw had iniated the concept of One Umma to gain mutual objective as mentioned in the early article of Sahifah Madinah. From the idea and vision perpective, the concept of One Malaysia Fullfils sunnah Rasulullah saw and equals with Islam demandas. To keep the aspect of implementation, the concept needs to be valued in accordance with the model and  pratice of One Umma conducted by Rasulullah Saw.